Analisis Praktek Keperawatan Maternitas Dengan Fokus Penerapan Tekhnik Pijat Oksitosin Pada Asuhan Keperawatan Ibu Post Partum Dengan Masalah Keperawatan Ketidakefektifan Menyusui - Fitri Nuriya Santi (LPPM Sikes Panca Bhakti Bandar Lampung, 2018)
Lack of milk production and expenditure in the first days after delivery can be caused by a lack of stimulation of prolactin and oxytocin that play a role in the smooth production and expenditure of breast milk. In the community especially in postpartum mothers who experienced insufficiency of breast milk expenditure did not know about the massage of oxytocin, so the mother immediately gave the baby breast milk because did not know that the milk's insufficiency can be overcome by oxytocin massage, oxytocin massage should not be done by health workers but can also be done by people closest to the client. Therefore, it is necessary to provide oxytocin massage to post partum mothers who experience insufficient milk expenditure for the production and smoothness of breast milk expenditure. The purpose of applying this intervention is to know the effect of oxytocin massage on post partum mothers to facilitate the expenditure of breast milk in the Pomegranate Room RSUD Dr. H. Abdul Moloek Lampung Province. Methods in implementing nursing practice using case study design is by implementing nursing care on post partum mothers with nursing ineffective breastfeeding problems. In four managed cases. From the results of research conducted for three days found the application of oxytocin massage effect on the production and fluency of breastfeeding expenditure on postpartum mothers who experienced insufficiency of breastfeeding and massage is recommended for post partum mothers who experienced insufficiency of breast milk expenditure.